Changes in Activity Participation Among Older Adults With Subjective Cognitive Decline or Objective Cognitive Deficits - Rotenberg, Shlomit; Maeir, Adina; Dawson, Deirdre R. (Frontiers in Neurology, 2020)
Participation in daily activities is crucial for healthy aging. There is limited research on participation of older adults with subjective cognitive decline (SCD), defined as the experience of cognitive deficits with no evidence of objective cognitive deficits. Therefore, this study examined perceived changes in participation in this population, and compared it to perceived changes reported by individuals with objective cognitive deficits. The study aimed to: (1) examine the reported changes in activity participation of older with SCD; (2) investigate differences in the reported changes in participation between individuals with SCD and those with mild or severe objective cognitive deficits; (3) examine the relationship between activity participation, subjective memory, and objective cognitive status; and (4) explore whether subjective memory explains additional variance in activity participation after accounting for age and objective cognitive deficits. Participants were 115 older adults (60+), divided into three groups based on their Montreal Cognitive Assessment (MoCA) scores: (1) SCD (MoCA≥26; n = 66); (2) mild objective cognitive deficits (MoCA = 20–25; n = 34); and (3) severe objective cognitive deficits (MoCA ≤ 19; n = 15). The Activity Card Sort was used to measure participation in instrumental activities of daily living, social, and leisure activities. The Multifactorial Memory Questionnaire—Ability subscale was used to assess subjective memory. We found that individuals with SCD, mild cognitive deficits and severe cognitive deficits reported participation withdrawal to a level of 80, 70, and 58% of their past participation, respectively. A significant between group difference was found on participation [χ2(2) = 16.44, p < 0.01], with the SCD group reporting higher participation than the other two groups. Participation significantly correlated with both cognitive status (r = 0.40, p < 0.01) and subjective memory (r = 0.45, p < 0.05). A regression analysis revealed that subjective memory contributed significantly to the explained variance in participation, beyond that accounted for by objective cognitive deficits and age. Our findings demonstrate the important role of subjective memory problems in activity participation of older adults, even in the absence of objective cognitive deficits.